2018
DOI: 10.1128/jcm.00009-18
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing for Characterizing Drug Resistance-Conferring Mycobacterium tuberculosis Genes from Clinical Isolates in the Ukraine

Abstract: The Ukraine ranks among the top 20 countries with the highest number of multidrug-resistant (MDR) and extensively drug resistant (XDR) cases in the world. However, little is known of the genetic diversity, i.e., resistance signatures, in clinical isolates from this region. We analyzed seven of most prevalent MDR/XDR antibiotic resistance-conferring genes from clinical isolates ( = 75) collected from geographically diverse Ukrainian oblasts and the southern Crimean peninsula. Genomic analysis revealed that 6 (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…A genetic analysis by next-generation sequencing performed in Ukraine. Daum et al found a poly-resistant strain of M. tuberculosis containing the amino acid substitutions W341R and R463L in KatG ( Daum et al, 2018 ), which are the same amino acid changes as strain CDC-A. A strain with MIC >1 mg/L found to have mutations at W341G and R463L by DNA sequencing ( Brossier et al, 2006 ); and a group in Brazil found a strain with an INH MIC >32 mg/L harbors KatG W341S ( Cardoso et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…A genetic analysis by next-generation sequencing performed in Ukraine. Daum et al found a poly-resistant strain of M. tuberculosis containing the amino acid substitutions W341R and R463L in KatG ( Daum et al, 2018 ), which are the same amino acid changes as strain CDC-A. A strain with MIC >1 mg/L found to have mutations at W341G and R463L by DNA sequencing ( Brossier et al, 2006 ); and a group in Brazil found a strain with an INH MIC >32 mg/L harbors KatG W341S ( Cardoso et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous challenges had to be addressed in the context of maternal referral process such as inability to communicate with tertiary referral hospital due to a poor cellular network, distance from the referral hospital, lack of a vehicle or ambulance by the referral institution were commonly cited [6,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally mutations that occur outside of genes that are known to be related to drug resistance can be identified from the entire TB genome. 9,10,15,16 In this paper, we focus on the drug resistance profile from the NGS data. Data analysis is performed using a bioinformatics approach.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of WGS data allows us to assess the genetic diversity across the genome, seeking signatures of selective pressure [5]. Many countries apply WGS for detecting MDR and XDR Tuberculosis [6][7][8][9][10][11][12][13]. Whole-genome sequencing of bacteria has been shown to provide comprehensive data like as prediction of drug susceptibility and resistance, epidemiological analysis and research [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation